Generation of an infectious cDNA clone for NADC30-like PRRSV - Qiao, Yang-Yang; Wang, Hai-Ming; Lu, Hui; Wang, Yong-Juan; Zhang, Wei; Gu, Hao; Cai, Xue-Hui; Xu, Qin-Se; Chen, Zhang-Yan; Tang, Yan-Dong (Frontiers in Veterinary Science, 2024)
The Porcine reproductive and respiratory syndrome virus (PRRSV) is a highly significant infectious disease that poses a substantial threat to the global pig industry.In recent years, the NADC30-like strain has gradually emerged as prevalent in China, causing a profound impact on the country's pig farming industry. Therefore, it is important to conduct an in-depth study on the characteristics and gene functions of the NADC30-like strain. An infectious cDNA clone is an indispensable tool for investigating the functions of viral genes. In this current study, we successfully isolated a NADC30-like strain and constructed its full-length infectious cDNA clone. The utilization of this clone will facilitate our investigation into the viral replication, pathogenesis, and immune response associated with the PRRSV NADC30-like strain.